Second stage surgery: a clinical report comparing efficacy of laser and electrocautery - Raghavan, Rohit; PA., Shajahan; Koruthu, Anil; Sukumar, B.; Nair, Anoop; KP., Divakar (International Journal of Dental Research, 2014)
Implant exposure for impression making in second stage surgery is a very important clinical step in implant rehabilitation. It can be done in three different ways; scalpel, electrocautery and lasers. With increasing number of dentists preferring to explore the modern technology, use of electro cautery and the lasers have become popular. However the choice between an electrocautery and laser is a difficult one. This clinical report employs both the modalities in the same patient and weighs pros and cons of each of them.   Keywords: Dental implant, Electrocautery, Laser, Second stage surgery.